2015
DOI: 10.11648/j.jfns.s.2015030301.12
|View full text |Cite
|
Sign up to set email alerts
|

Ginger-induced Ileal Motility is Modified by Stress: Sex Differences in Rats

Abstract: Abstract:Ginger is widely used as a spice and also an effective herbal medicine to treat gastrointestinal disorders. On the other hand, stress can induce various modulation of digestive motility. Here, we investigated ginger effects on stress-induced motility of the isolated ileum in male and female rats, in vitro. Rats (Wistar, SPF, 7-12 weeks of age, 148-393 g BW) were divided into Control (1G) and 3G groups. 3G stress (every day for 10 min) was loaded by centrifugal apparatus for 1, 3, 15 and 30 days. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous studies using isolated intestinal tract have reported that intrinsic pacemaker activity originates from ICCs of the Auerbach plexus, which are electrically coupled to smooth muscle cells [20,22]. ICCs play a major role in intestinal contraction without the involvement of motor neurons, hormones, or inflammatory mediators, and have been suggested to be modulated by several nutrients [23][24][25][26]. Another previous study reported an inhibitory action of caffeine on the smooth muscle contraction [27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using isolated intestinal tract have reported that intrinsic pacemaker activity originates from ICCs of the Auerbach plexus, which are electrically coupled to smooth muscle cells [20,22]. ICCs play a major role in intestinal contraction without the involvement of motor neurons, hormones, or inflammatory mediators, and have been suggested to be modulated by several nutrients [23][24][25][26]. Another previous study reported an inhibitory action of caffeine on the smooth muscle contraction [27].…”
Section: Introductionmentioning
confidence: 99%